In vitro Prebiotic Effects of Bamboo Shoots and Potato Peel Extracts on the Proliferation of Lactic Acid Bacteria Under Simulated GIT Conditions - Thakur, Kiran; Xu, Guan-Yi; Zhang, Jian-Guo; Zhang, Fang; Hu, Fei; Wei, Zhao-Jun (Frontiers in Microbiology, 2018)
The present study explored the possible prebiotic application of potato peel and bamboo shoot extracts for the proliferation of Lactic acid bacteria from diverse niches and their tolerance ability to simulated gastrointestinal conditions (GIT) was also examined. Initially, the complete 16S rDNA sequencing of selected isolates revealed them as Lactobacillus paracasei (6), Staphylococcus simulans (2), and Streptococcus thermophilus (1). Higher cell densities and rapid pH change were obtained from cultured media supplemented with BS (2%) and PP (2%) as a carbon source. Their higher tolerance and the lowest reducing sugar abilities were obtained for BS at pH 2.5 and 9.0, while, at pH 3.5 and 8.0 for PP. The isolates were screened for additional functional and technological properties to harvest the most appropriate starter. The selected isolates harbored promising functional properties such as amylase presence, cell surface hydrophobicity, auto-aggregation, proteolytic and lipolytic activity, antifungal action as well as exopolysaccharide production. On the basis of these attributes, microencapsulated strain K3 was found resistant to gastro-intestinal conditions after 2 h, resulting in significantly (p≤0.05) improved survival compared to non-capsulated strain. The current approach presents an interesting economical strategy to modulate LAB through supplementation of plant-derived carbon sources as well as to enhance their survival under GIT.